Overlooked flower-visiting Orthoptera in Southeast Asia - Tan, M.K.; Artchwakom, T.; Abdul Wahab, R.; Lee, C.Y.; Belabut, D.M.; Tan, H.T.W. (Pensoft Publishers, 2017)
The study of insect–plant interactions such as flower visitors, pollinators, and florivores, are important for understanding the natural world. However, not all flower-visiting insects are equally well known, especially in the biodiverse Southeast Asian region. One group is the orthopterans, comprising of grasshoppers, crickets, and katydids. Natural history observations were made around Southeast Asia to document flower-visiting orthopterans. Owing to the limited studies on the ecology of orthopterans in Southeast Asia, we provide here the first documentation of flower-visiting orthopterans from Southeast Asia and the most extensive one for the Tropics. Based on 140 incidences of orthopteran visiting flowers, 41 orthopteran species have so far been recorded to visit 35 different plant species, in mainly Singapore, Malaysia, part of Thailand, and Brunei Darussalam. We conclude that orthopterans are indeed overlooked flower-visitors in this region and warrant further investigation.